Pemberdayaan UMKM Nagi Sipadeh Melalui Digitalisasi Promosi Usaha Berbasis Website Di Kecamatan Sangir Kabupaten Solok Selatan - Ares Albirru Amsal; Lailaturrahmi Lailaturrahmi; Felga Zulfia Rasdiana (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
The challenge of digitalization is a major obstacle for MSMEs in South Solok Regency in expanding their market reach and building competitiveness. This community service program aims to strengthen the competitiveness of Nagi Sipadeh, a red ginger drink producer in Sangir District, through the use of simple, easily accessible digital technology. A participatory approach was applied in the implementation of the program, which consisted of several stages: observation and interviews to identify business needs, designing a promotional website based on Google Sites as a digital storefront and product information center, content management training to enable business owners to update information independently, and evaluating website utilization to measure the impact on digital visibility. The program results showed a 57% increase in online interactions through Google Reviews and an expansion of promotional reach after the website was integrated with social media. The website also strengthened business owners' digital literacy and enhanced their ability to manage online communication channels with consumers. Furthermore, the website provided an initial foundation for the development of broader digital marketing and promotional features. This program has proven effective in increasing business exposure, expanding market networks, and encouraging MSMEs' digital independence by utilizing simple technology. Continued efforts such as increasing digital marketing capacity and strengthening partnership networks will support more competitive business growth.